The Effect of Income on Child Development - Blau, David M. (The Review of Economics and Statistics, 1999)
This study presents estimates of the effect of parental income on children's cognitive, social, and emotional development. The effect of current income is small, especially when income is treated as endogenous. The effect of “permanent” income is substantially larger, but relatively small when compared to the magnitude of recent policy-induced changes in income. Family background characteristics play a more important role than income in determining child outcomes. Policies that affect family income will have little direct impact on child development unless they result in very large and permanent changes in income.